TRANSFORMATION OF CREATIVE ECONOMY SMEs IN KERIS PRODUCTION IN SUMENEP: PRESERVING CULTURAL HERITAGE WITHIN A SUSTAINABLE ECONOMIC FRAMEWORK - Nurdiana, Fitri; Muktirrahman, Muktirrahman; Sholehah, Nadelatus; Ilwatina, Ilwatina; Maksum, Maksum (Faculty of Islamic Economic and Business - Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstract: This study aims to analyze the digital transformation process of Micro, Small, and Medium Enterprises (MSMEs) in the creative economy producing keris in Sumenep, Madura, to preserve cultural heritage while promoting sustainable economic growth within Indonesia’s economic development framework. Keris craftsmen are part of the creative economy’s handicraft sub-sector, which has great potential in increasing economic added value through cultural heritage utilization. This research employs a qualitative-descriptive approach through in-depth interviews with keris craftsmen, observation of digitalization practices, and analysis of digital marketing strategies implementation in three main keris-producing sub-districts: Aeng Tong-Tong, Bluto, and Lenteng. The theoretical framework used includes Technology-Organization-Environment (TOE) for technology adoption analysis and Digital Storytelling Theory for cultural preservation through digital media. Digital transformation significantly expanded market reach by 45% and increased average transaction values from Rp 350,000 to Rp 550,000. Social media utilization achieved 12% engagement rates on TikTok, while e-commerce adoption through Tokopedia and Shopee enhanced product visibility and cultural storytelling capabilities. This study contributes to Indonesian economic development by demonstrating how cultural heritage-based MSMEs can leverage digital transformation to achieve sustainable economic growth, preserve intangible cultural heritage, and enhance Indonesia’s creative economy competitiveness in the global market. Keywords: digital transformation; MSMEs; creative economy; Sumenep keris; cultural heritage; sustainable economy Abstrak: Penelitian ini bertujuan untuk menganalisis proses transformasi digital Usaha Mikro, Kecil, dan Menengah (UMKM) ekonomi kreatif penghasil keris di Sumenep, Madura, untuk melestarikan warisan budaya sekaligus mendorong pertumbuhan ekonomi berkelanjutan dalam kerangka pembangunan ekonomi Indonesia. Pengrajin keris termasuk dalam sektor ekonomi kreatif subsektor kerajinan yang memiliki potensi besar dalam meningkatkan nilai tambah ekonomi melalui pemanfaatan warisan budaya. Penelitian ini menggunakan pendekatan kualitatif-deskriptif melalui wawancara mendalam dengan pengrajin keris, observasi praktik digitalisasi, dan analisis implementasi strategi pemasaran digital di tiga kecamatan utama penghasil keris: Aeng Tong-Tong, Bluto, dan Lenteng. Kerangka teoritis yang digunakan adalah Technology-Organization-Environment (TOE) untuk menganalisis adopsi teknologi dan Digital Storytelling Theory untuk pelestarian budaya melalui media digital. Transformasi digital secara signifikan memperluas jangkauan pasar sebesar 45% dan meningkatkan nilai rata-rata transaksi dari Rp 350.000 menjadi Rp 550.000. Pemanfaatan media sosial mencapai tingkat keterlibatan 12% di TikTok, sementara adopsi e-commerce melalui Tokopedia dan Shopee meningkatkan visibilitas produk dan kemampuan bercerita budaya. Penelitian ini berkontribusi pada pembangunan ekonomi Indonesia dengan menunjukkan bagaimana UMKM berbasis warisan budaya dapat memanfaatkan transformasi digital untuk mencapai pertumbuhan ekonomi berkelanjutan, melestarikan warisan budaya tak benda, dan meningkatkan daya saing ekonomi kreatif Indonesia di pasar global. Kata Kunci: transformasi digital; UMKM; ekonomi kreatif; keris Sumenep; warisan budaya; ekonomi berkelanjutan